A technology adoption and implementation process in an independent hotel chain. (August 2016) - Cobos, Liza M.; Mejia, Cynthia; Ozturk, Ahmet Bulent; Wang, Youcheng
Abstract: Successful technological initiatives in the hospitality industry are a product of a well-planned and executed innovation adoption process. This qualitative study investigated the adoption of radio frequency identification (RFID) enabled locking technology in an independent hospitality company as a mechanism for service innovation and improved internal process efficiency. Findings from the research generated themes significantly impacting the knowledge and persuasion stages of the diffusion of innovations (DOI) adoption process. Results produced theoretical implications which suggest the dual nature of adoption process in the service industries, as well as practical recommendations for the implementation of new technologies in the hospitality industry.